2015
DOI: 10.1038/cmi.2015.58
|View full text |Cite
|
Sign up to set email alerts
|

The rLrp of Mycobacterium tuberculosis inhibits proinflammatory cytokine production and downregulates APC function in mouse macrophages via a TLR2-mediated PI3K/Akt pathway activation-dependent mechanism

Abstract: We demonstrate that Mycobacterium tuberculosis recombinant leucine-responsive regulatory protein (rLrp) inhibits lipopolysaccharide (LPS)-induced tumor necrosis factor alpha (TNF-α), interleukin-6, and interleukin-12 production and blocks the nuclear translocation of subunits of the nuclear-receptor transcription factor NF-κB (Nuclear factor-kappa B). Moreover, rLrp attenuated LPS-induced DNA binding and NF-κB transcriptional activity, which was accompanied by the degradation of inhibitory IκBα and a consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 90 publications
0
30
0
Order By: Relevance
“…83 The Mtb recombinant leucine-responsive regulatory protein (rLrp) inhibits pro-inflammatory cytokine production and downregulates macrophage antigen presentation via TLR2mediated activation of the PI3K/AKT pathway. 84 Previous research from our lab revealed that Mtb-secreted proteins such as PtpA and Mce3E modulate TLR signaling by targeting the downstream molecules involved in the NF-κB and MAPK pathways. 85,86 Interestingly, a recent study demonstrated that G protein-coupled receptor 160 (GPR160) regulates mycobacteria entry into macrophages by activating MAPK/ERK signaling, which suggests a crosstalk between the GPCR and TLR signaling pathways during mycobacterial infection.…”
Section: Tlr Signalingmentioning
confidence: 98%
“…83 The Mtb recombinant leucine-responsive regulatory protein (rLrp) inhibits pro-inflammatory cytokine production and downregulates macrophage antigen presentation via TLR2mediated activation of the PI3K/AKT pathway. 84 Previous research from our lab revealed that Mtb-secreted proteins such as PtpA and Mce3E modulate TLR signaling by targeting the downstream molecules involved in the NF-κB and MAPK pathways. 85,86 Interestingly, a recent study demonstrated that G protein-coupled receptor 160 (GPR160) regulates mycobacteria entry into macrophages by activating MAPK/ERK signaling, which suggests a crosstalk between the GPCR and TLR signaling pathways during mycobacterial infection.…”
Section: Tlr Signalingmentioning
confidence: 98%
“…For instance, Akt-mediated GSK3 inactivation following stimulation of TLR2, 4, 5, or 9 with appropriate agonists (lipoteichoic acid, LPS or synthetic E. coli lipid A, flagellin, and human CpG, respectively) significantly suppressed pro-inflammatory cytokine secretion and induced (TLR2-dependent) IL-10 production in human monocytes in a CREB-and CREB-binding protein (CBP)-dependent manner [90]. In LPS-treated murine macrophage-like RAW264.7 cells and primary murine macrophages, preceding TLR2 stimulation by recombinant leucine-responsive regulatory protein preincubation results in PI3K/Akt activation, GSK3β-Ser9 phosphorylation, reduced NF-κB activity/nuclear translocation, and suppression of pro-inflammatory IL-6 and -12 expression [160]. In LPS-challenged human monocytes, it was shown that Akt-dependent GSK3 inactivation may be supported by additional mTORC2-dependent activation of Akt as well as (mTORC1-dependent) activation of GSK3β-Ser9-targeting S6K [161].…”
Section: Role Of Gsk3 During Bacterial Infectionsmentioning
confidence: 99%
“…The modulation of the intricate host signaling networks majorly governs the net observable responses. In this regard, it has been reported that alongside immunologically active pathways, many early development-specific signaling cascades are reprogrammed to furnish infection-defined defensive measures1213141516171819. One such pathway which is garnering attention is Hippo signaling pathway.…”
mentioning
confidence: 99%